2019
DOI: 10.1177/0894845319828543
|View full text |Cite
|
Sign up to set email alerts
|

ALAS: An Intervention to Promote Career Development Among Latina/o Immigrant High School Students

Abstract: This article describes the rationale, development, delivery, and evaluation strategy of a pilot career intervention program for immigrant Latina/o high school students: Advocating for Latina/o Achievement in School. This innovative intervention aims to prevent dropout and to promote academic success and college and career readiness through a combination of academic support and enhancing critical consciousness. Shorter term goals include increasing school-related self-efficacy expectations, school connectedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Lent and Brown (2013), for example, recognize career intervention as prevention and describe how social cognitive career theory (SCCT, Lent & Brown, 2013) can be integrated with multicultural psychology in the design of interventions that promote vocational hope and school performance and prevent school drop-out. McWhirter et al (2019) provide additional examples of the integration of SCCT, multicultural psychology, and critical psychology in youth-focused career intervention. Di Fabio et al (2017) describe how a range of psychological competencies drawn from career and self-construction theories (Savickas, 2013), SCCT (Lent & Brown, 2013), and psychology of working (Blustein, 2006) can be fostered to enable youth people to more effectively navigate normative career development tasks and cope with less predictable crises.…”
Section: Prevention and Vocational Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Lent and Brown (2013), for example, recognize career intervention as prevention and describe how social cognitive career theory (SCCT, Lent & Brown, 2013) can be integrated with multicultural psychology in the design of interventions that promote vocational hope and school performance and prevent school drop-out. McWhirter et al (2019) provide additional examples of the integration of SCCT, multicultural psychology, and critical psychology in youth-focused career intervention. Di Fabio et al (2017) describe how a range of psychological competencies drawn from career and self-construction theories (Savickas, 2013), SCCT (Lent & Brown, 2013), and psychology of working (Blustein, 2006) can be fostered to enable youth people to more effectively navigate normative career development tasks and cope with less predictable crises.…”
Section: Prevention and Vocational Psychologymentioning
confidence: 99%
“…From a broader wellness promotion perspective, higher levels of CC have also been associated with greater civic participation (Diemer & Li, 2011) and better mental health (Zimmerman et al, 1999) among high school students of color. Despite this encouraging data, the integration of CC into vocational intervention is limited to date (see Kenny, Blustein, et al, 2019; McWhirter et al, 2019; Perry et al, 2014, for exceptions). In addition, recent research also offers some caveats about how CC may be both beneficial and challenging for young people based on developmental level and other factors (Heberle et al, 2020).…”
Section: Applying the Psychology Of Working Theory In Youth-focused Pmentioning
confidence: 99%
“…Drawing from Prillentensky’s Emancipatory Communitarianism (1997) and Friere’s Pedagogy of the Oppressed (1970), a growing number of vocational psychologists and career development professionals are engaging in a postmodern assessment of the value and purpose of the career choice and decision-making paradigm (Blustein et al, 2005; Byars-Winston, 2014; Chronister et al, 2004; Diemer & Rasheed-Ali, 2009; Diemer & Blustein, 2006; Mcwhirter et al, 2019; Richardson, 1993; Solberg & Ali, 2017; Solberg, Howard et al, 2002). The application of Freire and Prillentensky’s ideas encourages vocational psychologists and career development professionals to consider whether and to what extent our program and service design strategies empower and liberate vulnerable populations.…”
mentioning
confidence: 99%
“…The fifth and final issue refers to the counselors’ attitudes toward social consciousness and social justice. The papers in this issue (Kenny, Blustein, Liang, Klein, & Etchie, 2019; McWhirter et al, 2019) suggested the importance of incorporating critical social consciousness into career education as an important resource for coping with both long-standing inequalities and massive changes in the world of work that contribute to ever-growing inequality. Incorporating social justice in career education involves understanding the social-contextual factors because issues of equity and equality relate to them and the need to learn diverse ways of social justice (Arthur, Collins, McMahon, & Marshall, 2009).…”
mentioning
confidence: 99%